Microwave amplifier design and analysis - Liao, Mengde (2015)
In recent years, non-Foster circuits are an active area for research purposes because they can handle tasks that a Foster network unable to do. Foster's reactance theorem is an im-portant theorem in the fields of electrical network analysis. A Foster circuit is supposed to be passive, thus an active circuit with a power source may not obey Foster’s theorem. They are known as non-Foster networks. [1]. Non-Foster circuits are being used in many applications. In my project, Negative capacitance circuit and Non-Foster match circuit for electri-cally small loop antenna were studied and reviewed firstly, and then the investigations of the two circuits were carried out to have the experimental results. The objective of the project is to understand the characteristics of the non-Foster circuits through the experiment process. The project consists of two main stages which are designing & simulation stage and building up & testing stage.